Mesenchymal stem cells from periapical lesions modulate cytokine production by local immune cells - Marković Milan; Tomić Sergej; Đokić Jelena; Mihajlović Dušan; Vučević Dragana; Gazivoda Dragan; Duka Miloš; Čolić Miodrag (Vojnosanitetski Pregled, 2018)
Background/Aim. Mesenchymal stem cells (MSCs) have been shown to suppress immune and inflammatory reactions. However, it is not known whether MSCs from inflammatory tissues, such as periapical lesions (PLs) have similar effects. This question was addressed in this study in which the aim was to examine the capacity of PL-MSCs for modulating cytokine production by local immune cells. Methods. PL-MSCs were isolated from asymptomatic (as) and symptomatic (sy) PLs. Their phenotype was analyzed by flow cytometry by detecting MSC surface markers. Anti-inflammatory and immunomodulatory properties of PL-MSCs were examined by measuring cytokine production in direct co-culture experiments with mononuclear cells (MNCs) isolated from asPLs and syPLs, respectively. The levels of cytokines in supernatants were determined by specific ELISA kits. Results. Both PL-MSCs lines were characterized by typical MSC phenotype, with the predominance of CD29, CD44, CD90, CD105 and CD166. However, the lines, independently of their similar phenotype had the same modulatory effect on cytokine production, but the response of asPL-MNCs and syPL-MNCs was different, in spite of similar composition of these MNCs. Both MSC lines inhibited the production of inflammatory cytokines, such as interleukin-1_ (IL-1_) and tumor necrosis factor-_ (TNF-_). However, IL-8 was only down-regulated in the co-culture of these MSC lines with syPL-MNCs. The PL-MSCs also modulated the production of immunoregulatory cytokines. Transforming growth factor-_ (TGF-_) was up-regulated by both as- and syPL-MNCs but IL-10 was up-regulated only by asPL-MNCs. Conclusion. Our results showed that PL-MSCs contribute to the restriction of local inflammatory and immune responses, but this effect is probably less efficient during the exacerbation of PL inflammation. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 175102]